2019
DOI: 10.1097/prs.0000000000005907
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Quality of Life following Reduction Mammaplasty in Adolescents and Young Women

Abstract: Background: Adolescent reduction mammaplasty remains controversial because of concerns of postoperative breast growth, complications, and the effect on well-being. The authors sought to prospectively quantify early and late complications following reduction mammaplasty in adolescents and young women, and examine the intersection of surgical complications and postoperative health-related quality of life. Methods: From 2008 to 2017, female patients aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 61 publications
0
58
1
Order By: Relevance
“…There are several known complications specific to this operation that include asymmetry, changes in nipple sensation, unattractive scars, diminished ability to breastfeed, and wound complications. [5][6][7] Wound complications include seroma, hematoma, dehiscence, infection, wound breakdown, skin necrosis, and nipple necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several known complications specific to this operation that include asymmetry, changes in nipple sensation, unattractive scars, diminished ability to breastfeed, and wound complications. [5][6][7] Wound complications include seroma, hematoma, dehiscence, infection, wound breakdown, skin necrosis, and nipple necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of symptomatic macromastia, patients report a high satisfaction rate after breast reduction surgery. [3][4][5] Unfortunately, the complications from the surgery can significantly disrupt a woman' s life due to previously unplanned hospital admissions, clinic appointments, wound care, time off work, and poor aesthetic outcome. Fac-ulty awareness of a large number of complications for patients after breast reduction surgery prompted the MRVAMC Plastic Surgery Service to establish a stricter surgical screening protocol using body mass index (BMI) values and negative nicotine status to help patients be healthier and reduce the potential risk before offering surgery.…”
mentioning
confidence: 99%
“…16 Moreover, Krucoff et al and Nuzzi et al found RM patients especially young women experience excellent breast-related QoL with high satisfaction with breasts and sexual wellbeing. 17,18 Crittenden et al reported statistically significant improvements in satisfaction with breasts, psychosocial well-being, sexual well-being and physical well-being scorings of patients with breast hypertrophy after RM in comparison to preoperative scores. 19 Recently, Silhol et al reported an inverse correlation between breast volume and sensibility in the preoperative evaluation, but disappeared after RM and Lin et al found the QoL of women underwent RM is significantly improved with special regard to pain, physical function and psychological function, and concluded that RM is an effective treatment for symptomatic breast hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Young women and adolescents, for whom body perception is more important, are more inclined to showing depressive symptoms. It is suggested that breast hypertrophy problem affects the bilateral relations or social relations negatively as a result of serious mental exposures in young women and adolescents 5,6,12 . Indeed, it is indicated that breast hypertrophy problem leads to risk in some adolescents such as eating disorder, bulimia nervosa, obesity, intentional vomiting, laxative and diuretic drugs, and suicidal thought 1,8,12,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of factors such as genetic predisposition and oversensitivity to estrogen is mentioned in the etiology of breast hypertrophy, this issue remains a mystery 2 . Breast hypertrophy is a disease that is encountered frequently in clinics, affects women's life multidimensionally, impairs the quality of life, and has mentally, physically, and socially negative effects [1][2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%